IDENTIFIKASI JENIS KAYU DALAM PEMBUATAN KERAMBA BERDASARKAN PERSEPSI MASYARAKAT DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Tiara Septa Yunanda; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Keramba is an alternative support of economy on society, so wood as the basic material need to be preserved. The purpose of this research to identify the species and criteria of wood which can be used on manufacturing keramba, based on public perception in Buluh Cina village. The method used on this research is purposivesampling. The analysis of the data used descriptive quantitative by interviewed local community in buluh cina village. Resultof the research showed that the species of wood used as basic material is, Cantleya corniculata Howard), Gluta rengas L, Dillenia grandifolia, Shorea Spp, Koompassia malaccensis. The criteria used for basicwood as keramba material is the diameter of tree 40-60 cm, high 15-20 m, length 2-4 m, and the level of wood alignment is 90-100 %. Keyword: the species of wood, criteria, public perception.